2021
DOI: 10.1007/s11695-021-05587-4
|View full text |Cite
|
Sign up to set email alerts
|

Bariatric Surgery as a Viable Treatment for Idiopathic Intracranial Hypertension: a Case Series and Review of Literature

Abstract: Purpose Idiopathic intracranial hypertension is a significant cause of preventable blindness. Patients suffer from debilitating headaches, pulsatile tinnitus, nausea, vomiting, photophobia and radicular pain. At this rate, treatment cost will increase to 462.7 million pounds sterling annually by 2030. Weight loss is the only proven disease-modifying therapy for reversal of idiopathic intracranial hypertension. Bariatric surgery leads to superlative weight loss and reversal of related comorbidities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…However, these studies were not comparable, and hence their findings cannot be used to directly compare the outcomes of bariatric and non-surgical weight loss interventions [ 10 ]. Another study has presented more accurate results by comparing non-surgical and surgical methods to reduce BMI and improve symptoms of IIH; this well-conducted systematic analysis with a large sample size has convincingly demonstrated the advantage of bariatric surgical interventions compared to non-surgical interventions in managing IIH based on a significant and steady reduction in the patient's BMI following the surgical approach [ 1 ]. However, despite the fact that there is a clear correlation between IIH and obesity, IIH is not generally accepted as an indication for bariatric surgery [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, these studies were not comparable, and hence their findings cannot be used to directly compare the outcomes of bariatric and non-surgical weight loss interventions [ 10 ]. Another study has presented more accurate results by comparing non-surgical and surgical methods to reduce BMI and improve symptoms of IIH; this well-conducted systematic analysis with a large sample size has convincingly demonstrated the advantage of bariatric surgical interventions compared to non-surgical interventions in managing IIH based on a significant and steady reduction in the patient's BMI following the surgical approach [ 1 ]. However, despite the fact that there is a clear correlation between IIH and obesity, IIH is not generally accepted as an indication for bariatric surgery [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study has presented more accurate results by comparing non-surgical and surgical methods to reduce BMI and improve symptoms of IIH; this well-conducted systematic analysis with a large sample size has convincingly demonstrated the advantage of bariatric surgical interventions compared to non-surgical interventions in managing IIH based on a significant and steady reduction in the patient's BMI following the surgical approach [ 1 ]. However, despite the fact that there is a clear correlation between IIH and obesity, IIH is not generally accepted as an indication for bariatric surgery [ 1 ]. Therefore, these patients will experience longer waiting periods for bariatric surgery, particularly in public health systems in which patients are frequently evaluated depending on their degree of obesity and comorbidity [ 1 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Weight loss is an essential part of the treatment for IIH, and it has been demonstrated that weight loss after a low-energy diet or after bariatric surgery is associated with complete remission or considerable improvement in the signs and symptoms associated with IIH (103,104,105,106). A recent randomized clinical trial with 66 women with obesity with IIH demonstrated that bariatric surgery was more effective than community weight management intervention in reducing intracranial pressure because of the greater sustained weight loss (107).…”
Section: Idiopathic Intracranial Hypertensionmentioning
confidence: 99%